1997
DOI: 10.1179/095066097790093190
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of FeAl

Abstract: Only in the last few years has considerable progress been made in obtaining reproducible mechanical properties data for FeAl. Two sets of observations are the foundation of this progress. The frrst is that the large vacancy concentrations that exist in FeAl at high temperature are easily retained at low temperature and that these strongly affect the iowtemperature mechanical properties. The second is that room temperature ductiiity is adversely affected by the presence of water vapor. The purpose of this paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(77 citation statements)
references
References 80 publications
3
74
0
Order By: Relevance
“…The ductile to brittle transition showed a clear dependence on the Al content and the deformation temperature. 12) In the present study the FeAl phase was found to be brittle when tested at strain rate of 0.5/s in the temperature range of 600-800°C. In this case the FeAl phase contained 5 at% Si.…”
Section: (C) and 4(f)) For Example The (111) Diffraction Spot Inmentioning
confidence: 98%
“…The ductile to brittle transition showed a clear dependence on the Al content and the deformation temperature. 12) In the present study the FeAl phase was found to be brittle when tested at strain rate of 0.5/s in the temperature range of 600-800°C. In this case the FeAl phase contained 5 at% Si.…”
Section: (C) and 4(f)) For Example The (111) Diffraction Spot Inmentioning
confidence: 98%
“…The proof stress of all of the FeAl alloy depicted in Fig. 4, more precisely B2 type FeAl alloy (1) , begins to decrease rapidly when the temperature exceeds around 700 -800 K, regardless of the existence of high strength reinforcements. Some models have been suggested to explain the relationship between the proof stress and the testing temperature of FeAl, for example cross-slip/pinning, anti-phase boundary mechanism, dislocation decomposition, vacancy hardening mechanism, and so on (1) .…”
Section: 2 Compression Testsmentioning
confidence: 99%
“…According to the XRD analyses of milled powders and compacts as shown in Fig. 2, matrix FeAl phase can be synthesized mostly by MA process, and the reinforcement, Al 2 O 3 or Fe 3 AlC, are synthesized during consolidation process up to 1 273 K. After 1 800 ks milling, the volume fractions of FeAl phase of both MA powders were about 70%, which were obtained by the rough estimation using the height ratio of the major peak (1) . Additionally, it is strongly affected by the presence of thermal vacancy whose concentration increases by increasing cooling rate after heat treatment.…”
Section: Fabrication Of In-situ Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…1, Al forms disordered solid solution in Fe up to about 11 wt.% of alloying; beyond this amount of Al, various intermetallic phases such as D0 3 -based Fe 3 Al and B2-based FeAl appear. These intermetallics are usually brittle in nature and have been the subject of thorough research [15][16][17] in the last decades of the 20th century, especially for high-temperature applications, with a view to replace stainless steels and Ni-based superalloys. Therefore, these materials will not be considered in this overview.…”
Section: Bulk Iron Alloysmentioning
confidence: 99%